Motivation, A Key Booster for Teachers’ Performance: A Case Study on Public Schools in North Macedonia - Ismaili, Diturije; Ollogu, Elisabeta Bajrami; Xhelili, Arta; Shaqiri , Kaltrina Zekolli (European Journal of Social Science Education and Research, 2024)
The quality of an educational system is closely connected with the quality of its teachers. Thus, research into the elementary teachers’ motivation is of a high importance. The main purpose of this study is to describe and identify the level of teachers’ motivation, factors influencing teachers’ motivation and its impact on teachers’ job performance in public elementary schools in the municipality of Chair, Republic of North Macedonia. Furthermore, this study examines teachers’ work consumption and organizational engagement as they relate to teaching performance. Teachers’ motivation was examined through focus groups with the principles of 10 elementary schools and a questionnaire administered to the teachers of elementary education. A sample of 319 teachers participated in the survey. The questionnaire was developed based on literature review. The findings of the study revealed that teachers’ high motivation is closely related to their students’ result. The factors that influenced teachers’ motivation were their salary level, the working conditions related to infrastructure and the interpersonal relations and communication with the leaders of the institutions and/or colleagues. After analysis numerous recommendations were given to help educational institutions provide better support to teachers and improve their levels of motivation and their job performance, such as providing a satisfying work infrastructure, key resources, and professional development opportunities, increasing salaries and giving acknowledgments and recognitions to motivate teachers’ and thus increase their job performance and satisfaction.